2017
DOI: 10.21873/anticanres.12126
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Matrix Metalloproteinase-7 Genotypes to the Risk of Non-solid Tumor, Childhood Leukemia

Abstract: Our results indicate that the MMP7 A-181G genotype interacts with age and gender and may serve as an early and predictive biomarker for childhood ALL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…In addition, MMP-8 C-799T, Val436Ala, or Lys460Thr may play a minor role in determining personal susceptibility of childhood ALL (27). As for MMP-7, variant genotypes at A-181G but not C-153T were associated with a higher risk of childhood ALL, especially among boys and those aged less than 3.5 years at onset (29). In the future, the contribution of the genotypes of other MMPs, especially those whose proteins were identified to be differentially expressed among ALL patients and healthy controls, will be helpful to reveal the role of ECM dysregulation in ALL etiology.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, MMP-8 C-799T, Val436Ala, or Lys460Thr may play a minor role in determining personal susceptibility of childhood ALL (27). As for MMP-7, variant genotypes at A-181G but not C-153T were associated with a higher risk of childhood ALL, especially among boys and those aged less than 3.5 years at onset (29). In the future, the contribution of the genotypes of other MMPs, especially those whose proteins were identified to be differentially expressed among ALL patients and healthy controls, will be helpful to reveal the role of ECM dysregulation in ALL etiology.…”
Section: Discussionmentioning
confidence: 98%
“…The questionnaire well recorded the disease history, diet and sleeping habits of the child in addition to the disease history, diet, behavioral lifestyle and socioeconomic status of the parents. Then, 266 ageand gender-matched healthy participants were chosen as the control group following initial random sampling from the Health Examination Cohort established as we have previously published (27)(28)(29). Most of the volunteers underwent health examinations every 5 to 6 months with no gap longer than one year.…”
Section: Methodsmentioning
confidence: 99%
“…All investigated subjects voluntarily participating in this study, completed a questionnaire form with the help of their parents or guardians, and provided their peripheral blood samples less than 5 ml without any uncomfortable feelings. An equal number of age-matched healthy subjects without any cancer were recruited as the control group in accordance with the method for initial random sampling established by the Health Examination Cohort over the similar period of 2005 to 2010 as we previously published (3)(4)(5). Most healthy subjects underwent health examinations every 5 to 6 months.…”
Section: Methodsmentioning
confidence: 99%
“…The molecular etiology of ALL is not completely understood. Genome-wide and candidate-gene association studies show that genetic polymorphisms of some susceptibility genes are associated with the personal susceptibility of childhood ALL (1)(2)(3)(4)(5). In recent years, it has been reported that microRNAs (miRNAs) may play an important role in the regulation of hematopoiesis (6).…”
mentioning
confidence: 99%
“…All investigated subjects voluntarily participated in this study, completed a questionnaire form with the help of their parents or guardians, and provided 5 ml of their peripheral blood samples without any uncomfortable feelings. An equal number of age-matched healthy subjects were recruited as the control group in accordance with the method for initial random sampling established by the Health Examination Cohort between 2005 to 2010 as previously described (29)(30)(31). Most of the healthy subjects underwent health examinations every 5 to 6 months.…”
Section: Methodsmentioning
confidence: 99%